Quality of Life for Diverse Older Adults in Assisted Living: The Centrality of Control. Issue 7 (16th November 2016) - Koehn, Sharon D.; Mahmood, Atiya N.; Stott-Eveneshen, Sarah
ABSTRACT: This pilot project asked: How do ethnically diverse older adult residents of assisted living (AL) facilities in British Columbia (BC) experience quality of life? And, what role, if any, do organizational and physical environmental features play in influencing how quality of life is experienced? The study was conducted at three AL sites in BC: two ethnoculturally targeted and one nontargeted. Environmental audits at each site captured descriptive data on policies, fees, rules, staffing, meals, and activities, and the built environment of the AL building and neighborhood. Using a framework that understands the quality of life of older adults to be contingent on their capability to pursue 5 conceptual attributes—attachment, role, enjoyment, security, and control — we conducted 3 focus groups with residents (1 per site) and 6 interviews with staff (2 per site). Attributes were linked to the environmental features captured in the audits. All dimensions of the environment, especially organizational, influence tenants' capability to attain the attributes of quality of life, most importantly control. Although many tenants accept the trade-off between increased safety and diminished control that accompanies a move into AL, more could be done to minimize that loss. Social workers can advocate for the necessary multi-sectoral changes.